Emission factors of trace gases and particles from tropical savanna fires in Australia. Issue 11 (10th June 2017) - Desservettaz, Maximilien; Paton‐Walsh, Clare; Griffith, David W. T.; Kettlewell, Graham; Keywood, Melita D.; Vanderschoot, Marcel V.; Ward, Jason; Mallet, Marc D.; Milic, Andelija; Miljevic, Branka; Ristovski, Zoran D.; Howard, Dean; et al.
Abstract: Savanna fires contribute significantly to global aerosol loading and hence to the Earth's radiative budget. Modeling of the climatic impact of these aerosols is made difficult due to a lack of knowledge of their size distribution. Australia is the third largest source of global carbon emissions from biomass burning, with emissions dominated by tropical savanna fires. Despite this, only a few previous studies have reported emission factors of trace gases from this important ecosystem and there are no previous published emission factors for the aerosol properties reported here for Australian savanna fires. In June 2014, the SAFIRED campaign (Savanna Fires in the Early Dry season) took place in the Northern Territory of Australia, with the purpose of investigating emissions and aging of aerosols from Australian savanna fires. This paper presents observed enhancement ratios and inferred emission factors of trace gases (CO2, CO, CH4, N2 O, and gaseous elemental mercury), particles over different size modes (Aitken and accumulation), and speciated aerosols components (organics, sulfate, nitrate, ammonium, and chloride). Nine smoke events were identified from the data using large enhancements in CO and/or aerosol data to indicate biomass burning event. The results reported in this paper include the first emission factors for Aitken and accumulation mode aerosols from savanna fires, providing useful size information to enable better modeling of the climatic impact of this important source of global aerosols. Key Points: First emission factors for Aitken and accumulation mode particles from savanna fires First emission factors for speciated aerosols from Australian savanna fires First emission factors for gaseous elemental mercury from Australian savanna fires